2008
DOI: 10.1016/j.rmed.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory capacity predicts mortality in patients with chronic obstructive pulmonary disease

Abstract: IC (%pred.) is a powerful functional predictor of all-cause and respiratory mortality and of exacerbation-related hospital admissions in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 29 publications
3
53
2
16
Order By: Relevance
“…On day 1 the proportion of subjects with reduced inspiratory capacity (Ͻ 80% of predicted 25 ) was the same as the percentage with inspiratory muscle dysfunction (suggested by Vilaró et al 7 , as P Imax Ͻ 70% of predicted), which is 13 subjects (68%). Indeed, the inspiratory capacity of patients with inspiratory muscle dysfunction was lower than that of patients without inspiratory muscle dysfunction (62% of predicted [53-72% of predicted] vs 93% of predicted [71-139% of predicted], respectively, P ϭ .02), and the classifications of reduced inspiratory capacity and inspiratory muscle dysfunction were associated (phi coefficient 0.62, P ϭ .03).…”
Section: Respiratory Muscle Strength During and After Hospitalizationsupporting
confidence: 69%
“…On day 1 the proportion of subjects with reduced inspiratory capacity (Ͻ 80% of predicted 25 ) was the same as the percentage with inspiratory muscle dysfunction (suggested by Vilaró et al 7 , as P Imax Ͻ 70% of predicted), which is 13 subjects (68%). Indeed, the inspiratory capacity of patients with inspiratory muscle dysfunction was lower than that of patients without inspiratory muscle dysfunction (62% of predicted [53-72% of predicted] vs 93% of predicted [71-139% of predicted], respectively, P ϭ .02), and the classifications of reduced inspiratory capacity and inspiratory muscle dysfunction were associated (phi coefficient 0.62, P ϭ .03).…”
Section: Respiratory Muscle Strength During and After Hospitalizationsupporting
confidence: 69%
“…Dyspnea score and muscle strength were also significantly decreased for patients in the BODE index quartile groups 3-4. Thus, we consider the GOLD stage is an unclear criteria for physical ability, which is similar the reports above [3][4][5][6][7][8] . According to Fabbri et al 26) , 14% of patients who were clinically diagnosed with COPD were actually categorized in GOLD stage 0 in which FEV 1.0 / FVC is 70% or higher and more and %FEV 1.0 is 80% or higher.…”
Section: Discussionmentioning
confidence: 67%
“…While it is known that there is a correlation between FEV 1.0 and prognosis 2) , FEV 1.0 is simply one of many indices. It has also been reported that the inspiratory capacity (IC), exercise capacity, dyspnea score and body mass index (BMI) exhibit stronger correlations with prognosis [3][4][5][6][7][8] . Recently, the BMI, airway obstruction, dyspnea score, and exercise capacity (BODE) index, which is an evaluation method considering the multidimensional symptoms of COPD, have been used 9) .…”
Section: Introductionmentioning
confidence: 99%
“…8 Static hyperinflation can be determined by measuring IC and/or the ratio of IC to total lung capacity (IC/TLC). [8][9][10] Its increase during exercise is defined as dynamic hyperinflation (DH). During exercise, as ventilatory demand increases in flow-limited patients, progressive air trapping and further DH above the already increased resting value is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…11,14-16 A few longitudinal studies have assessed the impact of pulmonary hyperinflation on the prognosis of COPD. Recently, 2 studies assessed the impact of static hyperinflation on mortality in COPD patients and found that it was an independent predictor of mortality 8,10 ; however, the possible value of DH in predicting survival has not been adequately evaluated.…”
Section: Introductionmentioning
confidence: 99%